1992
DOI: 10.1111/j.1439-0396.1992.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of level of dietary fibre from wheat bran on digestibility of nutrients, digestive enzymes and performance in the european Large White and Chinese Mei Shan pig

Abstract: Zusammenfassung Der Einfluß von Rohfaserkomponenten aus Weizenkleie auf die Verdaulichkeit der Nährstoffe, Verdauungsenzyme und Leistung von Large White‐ und chinesischen Mei Shan‐Schweinen Mit vierzehn kastrierten Large White (LW) und Mei Shan (MS)‐Schweinen im Lebendgewichtsbereich von 45–50 kg wurde ein Bilanzversuch (Versuch 1) zur Messung der scheinbaren Verdaulichkeit der Nährstoffe und der Rohfaserkomponenten durchgeführt. Mit 20 zusätzlichen Tieren wurde ein Versuch durchgeführt, um den Effekt von rohf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
5
28
1
1
Order By: Relevance
“…Nevertheless, there is controversial -E-mail: jose.aguilera@eez.csic.es information on the digestive capacity of indigenous pig breeds compared with lean-type pigs. Some authors have reported higher TTAD coefficients in obese-type pigs compared with lean pigs (Fé vrier et al, 1992;Freire et al, 2003). In contrast, Morales et al (2002) and Rivera-Ferre et al (2006) found lower TTAD coefficients for Iberian pigs (IB) when compared with Landrace pigs at the same stage of growth (fattening (90 to 110 kg BW) and post-weaning (25 to 35 kg BW) pigs, respectively), which may contribute to explaining the poorer nutrient utilization of the IB genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is controversial -E-mail: jose.aguilera@eez.csic.es information on the digestive capacity of indigenous pig breeds compared with lean-type pigs. Some authors have reported higher TTAD coefficients in obese-type pigs compared with lean pigs (Fé vrier et al, 1992;Freire et al, 2003). In contrast, Morales et al (2002) and Rivera-Ferre et al (2006) found lower TTAD coefficients for Iberian pigs (IB) when compared with Landrace pigs at the same stage of growth (fattening (90 to 110 kg BW) and post-weaning (25 to 35 kg BW) pigs, respectively), which may contribute to explaining the poorer nutrient utilization of the IB genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in diet composition, feed technology, animal development (BW) or animal breed can impact digestibility coefficients of nutrients and energy (Le Gall et al, 2009). With regard to breed effects, comparing Asian breeds with commercial European lines in pig has generally shown that commercial European lines have a lower digestive efficiency than Asian populations, especially when given fibrous feeds (Kemp et al, 1991;Fé vrier et al, 1992;Morel et al, 2006;Len et al, 2009a). On the other hand, recent selection experiments in pigs reported no difference in digestive efficiency between pigs divergently selected for residual feed intake (de Haer et al, 1993;Barea et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the use of maize cobs as a feed ingredient in pig nutrition is limited by high fibre (930 g neutral detergent fibre (NDF)/kg dry matter (DM); 573 g acid detergent fibre (ADF)/kg DM) and low protein (35.5 g crude protein (CP)/kg DM) contents (Viljoen, 1993;Ndindana et al, 2002;Kanengoni et al, 2004). High dietary fibre increases the rate of feed passage in the pig gut, and sequestrates nutrients in the fibre matrix, reducing their digestion (Stanogias & Pearce, 1985;Fevrier et al, 1992). Fibre levels in maize cobs should be reduced to improve their nutritive contribution to pig diets.…”
Section: Introductionmentioning
confidence: 99%